Weiterbildungswiderstand Eine kritische Theorie der Verweigerung - Holzer, Daniela (Pädagogik, 2017)
Recent years have shown an increase in learning and advanced education obligations. Yet it meets with open or covert resistance: Resisting adults question the participation in »the fetish of (further) education«.